2021
DOI: 10.3892/etm.2021.10681
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing TRAP1 sensitizes glioblastoma multiforme cells to temozolomide

Abstract: Glioma is a common malignant tumor of the central nervous system, accounting for ~50% of intracranial tumors. The current standard therapy for glioma is surgical resection followed by postoperative adjuvant radiotherapy and temozolomide (TMZ) chemotherapy. However, resistance to TMZ is one of the factors affecting prognosis. It has been reported that TNF receptor-associated protein 1 (TRAP1) is overexpressed in numerous types of tumor and that interfering with its function may abrogate chemotherapy resistance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Researchers found that suppressing the function of TRAP1 would benefit temozolomide therapy in GBM in vitro, revealed great potential and practical value in GBM treatment. [ 61 ]. CHP1, MAPK3, PRKAB2 and PRKAG2, these four genes, were rarely focused on.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers found that suppressing the function of TRAP1 would benefit temozolomide therapy in GBM in vitro, revealed great potential and practical value in GBM treatment. [ 61 ]. CHP1, MAPK3, PRKAB2 and PRKAG2, these four genes, were rarely focused on.…”
Section: Discussionmentioning
confidence: 99%
“…gastric cancer [15] and other cancers, and is involved in the drug resistance of rectal cancer, glioblastoma and other tumors [16,17] . Giuseppe et al [18] found that silencing TRAP1 could inhibit the progression of cell cycle of thyroid cancer, leading to cell necrosis and promote the sensitivity of cells to chemotherapeutic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that TRAP1 is involved in tumor progression by inhibiting apoptosis, promoting drug resistance and in maintaining energy supply under nutrient deprivation conditions [5] . TRAP1 has been reported to be associated with the drug resistance of ovarian cancer [6] , glioblastoma [7] and colon cancer [8] and so on, but whether it is involved in the drug resistance mechanism of lung cancer is still unclear. Therefore, this study intends to explore the relationship between TRAP1 and the energy supply pathway of lung cancer and its cisplatin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, both cell lines indicated a high degree of migration in the scratch assay. A whole exome sequencing for Jed66_GB indicated the presence of TC-rare damaging COSMIC variants detected in genes that were previously associated with glioblastoma including BCR activator of RhoGEF and GTPase ( BCR ) [ 43 , 44 ], TNF receptor associated protein 1 ( TRAP1 ) [ 45 – 47 ], DNA polymerase delta 1, catalytic subunit ( POLD1 ) [ 48 ], otopetrin 1 ( OTOP1 ) [ 49 ], tyrosine kinase 2 ( TYK2 ) [ 50 ], AT-rich interaction domain 1B ( ARID1B ) [ 51 ], CD48 molecule ( CD48 ) [ 52 ], ubiquitin specific peptidase 18 ( USP18 ) [ 53 ], nuclear receptor corepressor 1 ( NCOR1 ) [ 54 ], NFE2 Like BZIP Transcription Factor 2 ( NFE2L2 ) [ 55 ], and Kinesin Family Member 1A ( KIF1A ) [ 56 ]. For Jed41_GB, exome sequencing showed the presence of TC-rare damaging COSMIC variants detected in glioblastoma-associated genes including TP53 [ 43 , 44 , 57 ], LDL receptor related protein 1B ( LRP1B ) [ 44 , 58 ], adhesion G protein-coupled receptor E5 ( ADGRE5 ) [ 59 ], atrophin 1 ( ATN1 ) [ 60 ], autophagy related 2B ( ATG2B ) [ 61 , 62 ], MYC associated zinc finger protein ( MAZ ) [ 23 , 63 ], WNK lysine deficient protein kinase 1 ( WNK1 ) [ 64 , 65 ], UDP glucuronosyltransferase family 1 member A1 ( UGT1A1 ) [ 66 ], and UDP glucuronosyltransferase family 1 member A6 ( UGT1A6 ) [ 67 ].…”
Section: Discussionmentioning
confidence: 99%